2021
DOI: 10.1002/bse.2795
|View full text |Cite
|
Sign up to set email alerts
|

Does a sense of calling facilitate sustainability? Research on the influence of calling on employee green behavior

Abstract: Organizations recently attach growing importance to sustainable development and green human resource management (GHRM), raising research interest in predicting employee green behavior (EGB). However, the potential linkage between a sense of calling and EGB is neglected. This research fills the void by examining whether, how, and when calling predicts EGB. Drawing upon self‐determination theory, we argue that by satisfying three basic psychological needs (i.e., autonomy, competence, and relatedness), a sense of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 78 publications
0
16
0
Order By: Relevance
“…Likewise, Akhtar et al (2022) acknowledged that environmental‐related programmes help the HEIs to develop students' problem‐solving capabilities for addressing environmental issues. Thus, this implies that individual employees' increased environmental concern can shape their attitude towards environmentally friendly practices (Zhang et al, 2021). Based on this postulation, it is hypothesised thatHypothesis Environmental concern positively predicts attitude.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Likewise, Akhtar et al (2022) acknowledged that environmental‐related programmes help the HEIs to develop students' problem‐solving capabilities for addressing environmental issues. Thus, this implies that individual employees' increased environmental concern can shape their attitude towards environmentally friendly practices (Zhang et al, 2021). Based on this postulation, it is hypothesised thatHypothesis Environmental concern positively predicts attitude.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, employee green behaviour (EGB) is the sequence of employees' environmentally friendly activities that help achieve the objective of safeguarding the environment at the workplace (Al‐Swidi et al, 2021). Recent evidence contends that EGB influences the environmental performance (EP) of organisations (Ahmad et al, 2021; Nisar et al, 2021; Zhang et al, 2021). When employees align with the task of protecting the environment, the carbon emission level of organisations reduces, and this consequently bolsters environmental performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings indicated that the presence of a CC induces group members’ calling, a prosocial goal that drives them to exhibit cooperative behavior after their contact with CCs. Previous studies have found positive outcomes for calling, such as more green employee behavior, higher willingness to sacrifice for work, better work performance, and higher levels of life satisfaction ( Hall and Chandler, 2005 ; Bunderson and Thompson, 2009 ; Allan and Duffy, 2014 ; Zhang et al, 2021 ). Our study extends calling-related literature to the field of cooperation in a social context.…”
Section: Discussionmentioning
confidence: 97%
“…For instance, a study focusing on zookeepers indicated that employees with a high level of calling exhibit more willingness to sacrifice their free time (non-work time) for their organizations ( Bunderson and Thompson, 2009 ). Additionally, calling has been demonstrated to increase prosocial motivation in employees, which promotes green employee behavior ( Zhang et al, 2021 ). In general, when someone expresses a sense of calling, it suggests that the person consciously identifies with one’s prosocial goal.…”
Section: Introductionmentioning
confidence: 99%